Analisis Kontribusi Green Islamic Finance terhadap Pertumbuhan Ekonomi Berkelanjutan di Indonesia - Sarnada; Andika Saputra; Saniatul Hidayah; Amad Yani (Al-Maqashid: Journal of Economics and Islamic Business, 2026)
This study analyzes the contribution of Green Islamic Finance (GIF) to sustainable economic growth in Indonesia during the 2015–2024 period. Using a mixed-method approach with panel data regression analysis and qualitative descriptive analysis, this study integrates two theoretical frameworks that have often developed in parallel: sustainable finance and maqashid al-shariah. Data were obtained from reports published by the Financial Services Authority (OJK), Bank Indonesia (BI), and the Ministry of Finance of the Republic of Indonesia. The findings show that GIF instruments, particularly green sukuk, have a positive and significant effect on sustainable economic growth indicators, with a regression coefficient of 0.423 (p < 0.01). Every 10% increase in green sukuk issuance is associated with a 1.8% increase in the national Sustainable Development Index (SDI). The novelty of this study lies in the construction of a GIF composite index that simultaneously integrates environmental, sharia, and economic dimensions, an approach that has not been applied in previous studies. The policy implications highlight the importance of strengthening inclusive regulation and GIF literacy as a strategy to accelerate the transition toward a green economy based on Islamic values.